Demand-led research, biotechnology and the poor: Issues from the livestock sector - Heffernan, C.L. (TSAP and ILRI, 2006)
Demand, is the often quoted link between biotechnology development and poverty alleviation. Nonetheless, there is often little evidence as to the exact influence of demand on the research processes. Therefore, the following paper explores the perceptions vs. the reality of demand-led processes using examples from the livestock sector. First, an aspect of the literature, i.e. community-based delivery systems was evaluated using the core issues raised in the wider literature on demand. Second, the perspectives of 190 stakeholders were catalogued and disaggregated. The example from the literature demonstrated that independent views were largely in the minority with the discourse dominated by actors from donor-funded projects and programmes. The exploration of researcher perspectives demonstrated that while the researchers themselves, generally did not account for farmer demands, neither did they themselves appear to be driving research agendas. Thus, on a wider paradigmatic level, the risk is that notions of demand will simply mask the traditional drivers of biotechnology research with little overall impact on the poor.